Geochemical signatures and isotopic systematics constraining dynamics of fluoride contamination in groundwater across Jamui district, Indo-Gangetic alluvial plains, India. (August 2018) - Kumar, S.; Venkatesh, A.S.; Singh, Rambabu; Udayabhanu, G.; Saha, D.
Abstract: A data set of 76 water samples are obtained from surface and sub-surface water bodies to investigate chemical parameters and stable isotopic signatures in order to drive factors leading to fluoride (F − ) contamination in groundwater of parts of Jamui district, India. Hydrochemical facies reveals that F − concentration is lower in Ca 2+ -HCO3 - facies representative of recharge area, while discharge area has a tendency towards Na + -HCO3 - facies with elevated F − concentration. The ionic ratios Na + /Ca 2+ >1, Na + /Cl − >1, (Ca 2+ +Mg 2+ )/HCO3 − <1, Na + +K + = 0.5TZ + and Ca 2+ +Mg 2+ = TZ + witness silicate weathering by water-rock interaction coupled with ion exchange and prolonged residence time, are the principle factors for fluoride contamination (3.6 mg/L to 5.8 mg/L) in 67% of deeper bore wells. Geochemical modelling testifies excess of alkalinity due to the dominance of bicarbonate ion leading to calcite precipitation and dissolution of fluoride in solution contributing to fluoride contamination. The chemometric analysis reveals that the water chemistry of the study area is controlled by both anthropogenic and natural sources, and enrichment of fluoride in groundwater is possibly from geogenic source (fractured granite gneiss). The stable isotope plot shows that most of the samples fall along local meteoric water line indicating that the groundwater is originated from local precipitation with a possibility of evaporative enrichment. Groundwater enriched in δ 18 O is positively correlated with F − suggesting evaporation and longer residence time of water. Spatially elevated F − prevails in the eastern bank of Kiul River and along the groundwater flow direction, which is attributed to control of dynamics of hydrogeological conditions. Graphical abstract: Image 1 Highlights: F − contamination along the groundwater flow direction and discharge areas (Na + -HCO3 - facies). Elevated F − alongside enriched δ 18 O advocates longer residence time of water. CaCO3 precipitation and CaF2 dissolution constraining solute acquisition. Silicate weathering by water-rock interaction coupled with ion exchange. Chemometric analysis testifies plausible geogenic origine of F − in Groundwater.